The Peri-urban Areas of Metropolises, Key to Greening Policies for Improving the Living Environment of Citizens - Wiesztort, Laurène (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Increasingly dense cities have substituted natural and agricultural spaces for urban sprawl, and inhabitants have expressed their discomfort. As a result of this finding, the first questions about cities were brought up in 1950 to analyze sustainable development and global warming as fundamental issues for research in order to improve the urban environment and make cities more sustainable and livable. The conclusions are alarming and, therefore, new greening policies are emerging, but how to achieve greening in dense cities? What kind of nature? Where? For whom? This article intends to inventory, observe, and assess these large projects to tackle this problem. The method is based on literature and concept analyses and fieldwork to understand the evolution of policies, projects, and challenges since the 1950s. We address the concepts of green belts, green infrastructures, green and blue frames, and linear parks initially designed in the heart of metropolises. Finally, we review recent projects of our interest, mainly two.